The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2000
DOI: 10.1111/j.1572-0241.2000.03199.x
|View full text |Cite
|
Sign up to set email alerts
|

The importance of diagnostic accuracy in colonic inflammatory bowel disease

Abstract: There is significant interobserver variation in the histological diagnosis of colonic IBD. This may have a profound effect on clinical patient care and, especially, on the choice of operation. More accurate diagnostic criteria are needed to facilitate patient care and to optimize treatment outcome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
78
0
7

Year Published

2002
2002
2015
2015

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 163 publications
(89 citation statements)
references
References 31 publications
1
78
0
7
Order By: Relevance
“…In approximately 5% of IBD cases, a definite diagnosis of UC or CD cannot be established due, most commonly, to either insufficient clinical, radiologic, endoscopic or pathologic data, or because of prominent overlapping features between these two disorders (5)(6)(7)(8). Under these circumstances, the term "indeterminate" colitis (IC) has been used.…”
Section: Definitionmentioning
confidence: 99%
See 2 more Smart Citations
“…In approximately 5% of IBD cases, a definite diagnosis of UC or CD cannot be established due, most commonly, to either insufficient clinical, radiologic, endoscopic or pathologic data, or because of prominent overlapping features between these two disorders (5)(6)(7)(8). Under these circumstances, the term "indeterminate" colitis (IC) has been used.…”
Section: Definitionmentioning
confidence: 99%
“…Naturally, the prevalence of establishing a "diagnosis" of IC is highly dependent on the level of awareness of the reviewing pathologist regarding the wide range of morphologic features that can be seen in IBD. For instance, in a recent study by Farmer et al, 84 IBD colectomy specimens were reviewed by 24 university pathologists and the diagnostic accuracy was compared to a single GI pathologist who has a particular interest in IBD (7). Not unexpectedly, the GI pathologist rendered a diagnosis that was different from the others in 45% of specimens, and in most cases, it resulted in a change of diagnosis from UC to CD.…”
Section: Diagnosismentioning
confidence: 99%
See 1 more Smart Citation
“…5,6 For instance, in an informal survey of 10 GI pathologists (unpublished data), five pathologists defined IC as ''IBD: unclear if UC or Crohn's pathologically'', three defined it as ''acute fulminant colitis (with fissures),'' and two defined it as ''IBD, unclear either clinically and pathologically.'' Of the 10 GI pathologists, 8 believed that this diagnosis should only be rendered in resection specimens, but two suggested that it can be rendered in biopsies as well, a practice that is not recommended (see below).…”
Section: General Comments Definition and Terminologymentioning
confidence: 99%
“…3,5 The frequency of establishing this diagnosis is often related to the level of awareness of the broad spectrum of pathologic features that may occur in UC and CD (see below section on causes of uncertainty in IBD pathology). For instance, in a study by Farmer et al, 6 24 university medical center pathologists from 8 institutions evaluated 84 colectomy specimens and 35 sets of biopsies from 119 consecutive patients with colonic IBD. An experienced IBD pathologist subsequently reviewed these cases without knowledge of clinical data or the patient's prior diagnosis, and rendered his own diagnosis.…”
Section: General Comments Definition and Terminologymentioning
confidence: 99%